2015
DOI: 10.1002/anie.201504511
|View full text |Cite
|
Sign up to set email alerts
|

A Desulfonylative Approach in Oxidative Gold Catalysis: Regiospecific Access to Donor‐Substituted Acyl Gold Carbenes

Abstract: Donor-substituted acyl gold carbenes are challenging to access selectively via gold-promoted intermolecular oxidation of internal alkynes as the opposite regioisomers frequently predominate. By using alkynyl sulfones or sulfonates as substrates, the oxidative gold catalysis in the presence of substituted pyridine N-oxides offers regiospecific access to acyl/aryl, acyl/alkenyl or acyl/alkoxy gold carbenes by in situ expulsion of sulfur dioxide. The intermediacies of these reactive species are established by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 60 publications
1
28
1
2
Order By: Relevance
“…The results illustrated in equations 1–3 underscore the importance of the sulfonyl group: 1 ad furnished the diketone product 6 a whereas alkynylketone 1 ae and phosphonyl alkyne 1 ag showed no reactivity under the same reaction conditions. The formation of 6 a was attributed to the fact that the corresponding gold carbene intermediate is electron rich, which makes it easily oxidized by N ‐oxide …”
Section: Methodsmentioning
confidence: 99%
“…The results illustrated in equations 1–3 underscore the importance of the sulfonyl group: 1 ad furnished the diketone product 6 a whereas alkynylketone 1 ae and phosphonyl alkyne 1 ag showed no reactivity under the same reaction conditions. The formation of 6 a was attributed to the fact that the corresponding gold carbene intermediate is electron rich, which makes it easily oxidized by N ‐oxide …”
Section: Methodsmentioning
confidence: 99%
“…One of the prominent properties of gold(I) complexes is their ability to activate alkynes for nucleophilic additions . It was recently shown that this mode of reactivity can also be used for reactions of alkynes with oxidizing agents such as pyridine N‐ oxide or its derivatives . The reaction formally leads to gold‐α‐oxocarbenes that can be utilized in subsequent reactions .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] It was recently shown that this mode of reactivity can also be used for reactions of alkynes with oxidizing agents such as pyridine N-oxide or its derivatives. [3,4] The reactionf ormally leads to gold-a-oxocarbenes that can be utilized in subsequentr eactions. [5] The first intermolecular reactiono fg old-a-oxocarbenes was coupling with nitriles leadingt oo xazole rings (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[7] In particular, Zhang and others have established gold-catalyzed intermolecular oxidation approaches with NÀObond oxidants (Scheme 1c). [8] The in situ generated a-oxo gold carbenes undergo typical carbene transformations,s uch as cyclopropanation, XÀH bond insertion, 1,2-migration and ylide reaction, which renders readily available alkynes as effective alternatives of a-carbonyl diazo compounds.A side from intramolecular approaches,s everal reports also highlight the intermolecular trapping process of a-oxo gold carbenes generated with external oxidants. [9] In connection to our interest in cross-coupling with carbene precursors,w econceived the possibility of incorporating intermolecular oxidation of aC À Ct riple bond with acarbene migratory insertion process to achieve oxygenative coupling.However,compared to gold, palladium is aweaker Lewis acid when activating CÀCt riple bonds.…”
mentioning
confidence: 99%